Pengaruh Penanaman Modal, Sektor Ekonomi, dan Kredit terhadap Pertumbuhan Inklusif di Indonesia - Andini Adisti; Maizul Rahmizal (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Study This analyze influence foreign direct investment, domestic investment, financial sector , trade , and access credit to growth inclusive on level provinces in Indonesia during 2019–2023 period . With use method cross-section panel data regression and effect models remains the chosen one based on chow test and hausman , research This integrating the Solow model, theory growth inclusive , as well as theory development finance through credit channel . Results analysis show that variables investment And sector finance play a role significant in push growth inclusive. In a way policy , research This recommend strengthening relatedness domestic investment , expansion inclusion credit for MSMEs, as well as integration policy trading And financing area use support growth better economy evenly And sustainable throughout Indonesian territory .